The pharmacological and anatomical substrates of the amphetamine response in the rat. - Creese, I; Iversen, S (1975)
Bilateral 6-hydroxydopamine microinjections into the substantia nigra abolished both the locomotor and stereotyped responses to d-amphetamine in adult rats. The lesions resulted in a depletion of over 99 per cent of striatal tyrosine hydroxylase activity (indicating a near total lesion of the nigro-striatal dopamine pathway) as well as severe noradrenaline depletions. However, lesion of the dorsal or ventral noradrenergic pathways resulted in similar noradrenaline depletions but with no effect on striatal tyrosine hydroxylase levels and without the concomitant blockage of the amphetamine response. The substantia nigra lesioned rats were behaviourally supersensitive to apomorphine and L-DOPA and did not show a locomotor response to cocaine. The substantia nigra lesioned rats were not aphagic or adipsic. It was concluded that both the locomotor and stereotyped responses induced by amphetamine are dependent on the functional integrity of the nigro-striatal dopamine pathway.